The Influence of Web-Based Emaze Media on Student Learning Outcomes in History Subject Class XI SMA Negeri 1 Montasik - Risma Daiyanti; Nurasiah; Abdul Azis (Universitas Syiah Kuala and Collaboration Yayasan Yusda Edu Indonesia, 2025)
Learning outcomes are often a barrier to achieving learning goals. The use of various interesting media during the learning process can improve student learning outcomes. This study aims to find out the application of Web-based Emaze learning media in grade XI of SMA Negeri 1 Montasik and to find out how much influence Web-based Emaze learning media has on the learning outcomes of grade XI students of SMA Negeri 1 Montasik. This study uses a quantitative approach with a type of pre-experimental design research in the form of one group pretest posttest design where there is only one group. The population in this study is all grade XI students totaling 6 classes. The sample in this study is 25 students in class XI.3 with sampling using purposive sampling techniques. The data collection techniques used are observation, tests, and documentation. In the data analysis technique, the normality test, the homogeneity test, and the t-test differ from the two averages. The average score result before using Web-based Emaze media was 52.8 categorized as low and after being treated with a student's average score of 76 was categorized as high, this proves that there has been a significant change in student learning outcomes. Based on the results of the > test score or 12,889 > 1,714 at the significance level of α = 5% (0.05), it was rejected and accepted or there was a real (significant) influence on student learning outcomes before and after using Web-based Emaze learning media in History subjects. Thus, the use of Web-based Emaze learning media has an effect on the learning outcomes of History students in grade XI.3 at SMA Negeri 1 Montasik.